Fostering Trust and Loyalty in E-Commerce through Ethical Data Practices (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This conceptual paper examines how ethical data practices foster consumer trust and loyalty in e-commerce, with particular emphasis on data privacy, data security, and consumer perceived risk. As digital platforms increasingly depend on personal and behavioural data for personalisation, payment processing, targeted marketing, and customer engagement, consumer concerns regarding transparency, informed consent, unauthorised data sharing, cybersecurity, and manipulative data use have become central to online exchange relationships. Drawing on Social Exchange Theory, the paper proposes that consumers are more willing to maintain relationships with e-commerce platforms when the exchange of personal data for convenience and personalised services is perceived as fair, beneficial, secure, and trustworthy. The paper distinguishes ethical data governance from regulatory compliance by arguing that lawful data processing represents only a minimum threshold, whereas ethical governance also requires fairness, proportionality, accountability, respect for autonomy, and consideration of consumer wellbeing. An integrated conceptual framework is developed in which ethical data practices strengthen consumer loyalty through consumer trust, while perceived privacy and security risk weakens the positive relationship between ethical data practices and trust. The discussion also considers emerging governance challenges associated with generative artificial intelligence, algorithmic personalisation, blockchain, and decentralised identity systems. The paper contributes to e-commerce and business ethics literature by explaining how, and under what conditions, responsible data governance supports sustainable digital relationships. Practical implications are presented for managers, marketers, IT teams, policymakers, and consumers, together with measurable constructs and empirical testing directions for future research.